Welcome to Information Science Sponsored by SIG‐HFIS. Issue 1 (13th October 2021) - Hartel, Jenna; Bates, Marcia J.; Bhattarai, Vishma; Gray, LaVerne; Keilty, Patrick
Abstract: This panel engages conference attendees in the history and foundations of information science and provides an opportunity to reflect upon our field's current and future identity(s). It enacts the following scenario: At an orientation event for an information science program a spokesperson gives incoming students a brief address on the theme, "Welcome to information science." Six imaginative but authentic versions of that talk are offered here. To showcase the variety of approaches to information science across the past century, each disquisition is inspired by the work of one luminary, namely: Paul Otlet, S. R. Ranganathan, Jesse H. Shera, Elfreda Chatman, and Marcia J. Bates. In an effort to encourage a more spacious information science, an indigenous perspective on ways of knowing is also included. Attendees to this session will time‐travel across almost 100 years of information science history and ultimately rest in the reality of a multi‐perspective discipline.